The Influence Of Transformational Leadership, Job Satisfaction, And Work Motivation On Organizational Commitment (Study On Bendega Restaurant Employees) - Ida Bagus Putra Satya Dharma; I Gusti Made Suwandana (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
The culinary industry is currently growing rapidly in Indonesia, especially in restaurants that are easily found with a variety of dishes. One of them is Bendega Restaurant, which emerged along with the growth of the culinary business in the city of Denpasar. The existence of Bendega Restaurant stalls continues to survive amid the onslaught of the emergence of many restaurants. This study aims to determine whether work motivation can affect organizational commitment at Bendega Restaurant. The sample in this study was 54 respondents obtained based on the total employees of Bendega restaurant as many as 54 employees. Data was collected through interviews and surveys. The collected data were analyzed by classical assumption test, multiple linear regression analysis, coefficient of determination, simultaneous test, and partial test. The results of this study indicate that transformational leadership has a positive and significant effect on organizational commitment in Bendega Restaurant employees, job satisfaction has a positive and significant effect on organizational commitment in Bendega Restaurant employees, and work motivation has a positive and insignificant effect on organizational commitment in Bendega Restaurant employees. The implications of this research are divided into two, namely theoretical and practical. The theoretical implications of this study support the theory of organizational commitment. Practical implications support that transformational leadership can increase employee organizational commitment.